2020
DOI: 10.1002/pd.5726
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental impairment at 3 years of age after fetoscopic laser surgery for twin‐to‐twin transfusion syndrome

Abstract: BackgroundData on neurodevelopmental outcomes of children surviving after fetoscopic laser surgery (FLS) for twin‐to‐twin transfusion syndrome (TTTS) are scarce.MethodsWe retrospectively investigated children surviving after FLS for TTTS at 16 to 26 weeks' gestation between 2003 and 2014. Children were evaluated by standardized neurologic examinations using the Kyoto Scale 2001 at a corrected age of 3 years ± 6 months. Neurodevelopmental impairment (NDI) was defined as cerebral palsy (CP), bilateral blindness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Study or subgroup Lopriore (2009) 11 Tosello (2014) 9 Sananès (2016) 10 Korsakissok (2018) 22 Gijtenbeek (2020) 14 Matsushima (2020) 23 11 Tosello (2014) 9 Sananès (2016) 10 Korsakissok (2018) 22 Gijtenbeek (2020) 14 Gijtenbeek (2020) 14 Matsushima (2020) 23 11 Sananès (2016) 10 Korsakissok (2018) 22 Matsushima (2020) 23 difference, -343.26 g (95% CI, -470.59 to -215.92 g); P < 0.00001, I 2 = 27%). No significant difference was seen in the rate of SGA (P = 0.14) or cotwin demise (P = 0.77) between the NDI and non-NDI cases.…”
Section: Obstetric Variables As Risk Factors For Ndimentioning
confidence: 99%
See 1 more Smart Citation
“…Study or subgroup Lopriore (2009) 11 Tosello (2014) 9 Sananès (2016) 10 Korsakissok (2018) 22 Gijtenbeek (2020) 14 Matsushima (2020) 23 11 Tosello (2014) 9 Sananès (2016) 10 Korsakissok (2018) 22 Gijtenbeek (2020) 14 Gijtenbeek (2020) 14 Matsushima (2020) 23 11 Sananès (2016) 10 Korsakissok (2018) 22 Matsushima (2020) 23 difference, -343.26 g (95% CI, -470.59 to -215.92 g); P < 0.00001, I 2 = 27%). No significant difference was seen in the rate of SGA (P = 0.14) or cotwin demise (P = 0.77) between the NDI and non-NDI cases.…”
Section: Obstetric Variables As Risk Factors For Ndimentioning
confidence: 99%
“…All included studies were published between 2009 and 2020. Three studies were conducted in France 9,10,22 , two in The Netherlands 11,14 , two in Australia 8,12 , one in Japan 23 and one in Germany 13 . Three studies were prospective 10,12,22 , five studies were retrospective 8,9,11,14,23 and the design of one study was not reported 13 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Third, we only reported the short-term outcomes with some procedural parameters. The long-term outcomes and the results of neurological examinations are very important for thoroughly assessing the surgical technique (Matsushima et al, 2020;Rossi et al, 2011). One strength of our study is the relatively large cohort for comparing the rates of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Gross motor, ne motor, social development, adaptiveness, and language skills were the ve subdomains assessed in this study. An overall general DQ score was calculated by summing these subdomains, and more than 85 is considered normal (13).…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%